La incidencia de la gestión financiera en el desarrollo de las microempresas manufactureras de la parroquia tarqui en la ciudad de Guayaquil - Olivo Orellana, Mariuxi Yesenia (2019)
The present article analyzes the incidence of the financial management and the effective administration of the resources as a means to avoid insolvency, market instability, and he fulfillment of the organizational objectives.